The global transcriptional response of a raw starch-degrading amylolytic Saccharomyces cerevisiae strain to oxygen limitation and genetic modification - (:unkn) unknown (My University, 2016)
0

This study investigates the global transcriptional response of Saccharomyces cerevisiae strain WTPB-G, which was developed by transforming laboratory strain FY23 with the pPB-G plasmid expressing the Bacillus subtilis α-amylase and the Aspergillus awamori glucoamylase as a fusion protein. Genome-wide analysis of transcript levels revealed the cellular mechanisms and the related pathways that were affected by the genetic modification, which conferred the ability of starch utilization to wild-type cells by the introduction of a plasmid-harboring gene encoding the amylolytic activity. Fermentations were carried out in media containing glucose as the only carbon source under aerated and microaerated conditions, and the effect of aeration was also investigated in terms of fermentation properties and transcriptional response. The genome-wide gene expression analysis highlighted that plasmid replication induced cell wall organization and biogenesis, and repressed approximately 20% of the genes involved in ribosome biogenesis and RNA processing. Although oxygen limitation was found to be less effective in the transcriptional changes, a link between oxygen limitation and genes involved in oxidation-reduction, pH reduction, phosphate-containing compounds, and lipid and fatty acid processes was observed.
Keywords: Biyoloji